Edukasi Literasi Keuangan Sejak Dini pada Anak Usia Sekolah Dasar (Jurnal Manajemen dan Ekonomi (JME), 2024)
Introduction and education about financial literacy has not been provided in a precise and planned manner because it is considered something that is not important or even not needed by children. Parents still think talking about money in front of their children is taboo, this results in children not being ready to learn financial management from an early age. This research aims to provide financial literacy education from an early age to elementary school age children. This type of research is qualitative descriptive research. The research method used is literature study. This is done by looking for relevant reference sources, whether from previous articles, books or other sources. The research results show that, 1) how to provide financial literacy education to elementary school age children can be done by: (a) socializing financial literacy education, (b) story telling, (c) saving practice simulations, (d) games, and ( e) educational tour to the Indonesian banking museum. 2) giving pocket money to elementary school students by their parents can be an effort to train financial literacy from an early age. 3) saving behavior as a result of financial literacy education for elementary school students
Keywords: financial literacy education, elementary school age children, saving, pocket money